Over my dead body : unearthing the hidden history of America's cemeteries - Melville, Greg (Abrams Press, 2023)
"A lively tour through the history of US cemeteries that explores how, where, and why we bury our dead. The summer before his senior year in college, Greg Melville worked at the cemetery in his hometown, and thanks to hour upon hour of pushing a mower over the grassy acres, he came to realize what a rich story the place told of his town and its history. Thus was born Melville's lifelong curiosity with how, where, and why we bury and commemorate our dead."